Combinatorial Synthesis, Screening, and Binding Studies of Highly Functionalized Polyamino-amido Oligomers for Binding to Folded RNA - Pokorski, Jonathan K.; Appella, Daniel H. (Journal of Nucleic Acids, 2012)
Folded RNA molecules have recently emerged as critical regulatory elements in biological pathways, serving not just as carriers of genetic information but also as key components in enzymatic assemblies. In particular, the transactivation response element (TAR) of the HIV genome regulates transcriptional elongation by interacting specifically with the Tat protein, initiating the recruitment of the elongation complex. Preventing this interaction from occurring in vivo halts HIV replication, thus making RNA-binding molecules an intriguing pharmaceutical target. Using α-amino acids as starting materials, we have designed and synthesized a new class of polyamino-amido oligomers, called PAAs, specifically for binding to folded RNA structures. The PAA monomers were readily incorporated into a 125-member combinatorial library of PAA trimers. In order to rapidly assess RNA binding, a quantum dot-based fluorescent screen was developed to visualize RNA binding on-resin. The binding affinities of hits were quantified using a terbium footprinting assay, allowing us to identify a ligand (SFF) with low micromolar affinity (kd=14 μM) for TAR RNA. The work presented herein represents the development of a flexible scaffold that can be easily synthesized, screened, and subsequently modified to provide ligands specific for binding to folded RNAs.